Biocompatibility and adhesion response of magnesium-hydroxyapatite/strontium-titania (Mg-HAp/ Sr-TiO2) bilayer coating on titanium. (21st March 2022) - Praharaj, Rinmayee; Mishra, Snigdha; Misra, R. D. K.; Rautray, Tapash R.
ABSTRACT: Anodisation with electrochemical cathodic deposition method was employed to modify the surface of Ti implants with a bilayer coating made of Sr- doped titania (Sr-TiO2 ) and hydroxyapatite doped with magnesium (Mg-HAp). The Mg-HAp/Sr-TiO2 bilayer coating was compared with pure TiO2 and Sr-TiO2 single-layer coating. The Sr incorporation into TiO2 and Mg substitution into HAp strengthened their bioactive properties. The tensile test indicated increase in the mechanical strength of the bilayer coated substrate compared to pure TiO2 substrate. Moreover, the study indicated that the Sr and Mg ions were uniformly incorporated into the Mg-HAp/Sr-TiO2 bilayer coating with significantly higher roughness and hydrophilicity compared to the control. In vitro studies with osteoblasts cells had a superior response to the Mg-HAp/Sr-TiO2 bilayer surface. It was found that a bilayer Mg-HAp/Sr-TiO2 coating on Ti implants promotes bioactivity and has superior adhesion strength necessary for osseointegration and bone healing.